COVID-19 and Pro-environmental Behaviour at Destinations Amongst International Travellers - Calder, Gary; Radic, Aleksandar; Ryu, Hyungseo Bobby; Ariza-Montes, Antonio; Han, Heesup (Frontiers in Psychology, 2022)
This paper investigates the COVID-19 pandemic, and its impact on pro-environmental behaviour of individuals travelling internationally for leisure and recreational purposes. The aim of this manuscript is to investigate a conceptual framework created through the examination of current existing literature in the field of tourism science. The conceptual framework, consisting of certain constructs of the health belief model (HBM), and the theory of planned behaviour (TPB), is applied and tested using a partial least-squares-structural equation modelling (PLS-SEM). Data were collected from participants who have travelled internationally before and during the outbreak of the COVID-19 pandemic, and those who plan to travel post-COVID-19 pandemic. Results revealed that the conceptual framework tested positively against existing theory, highlighting the key influencing factors in which COVID-19 is likely to have on future pro-environmental behaviour of individuals travelling internationally for leisure and recreational purposes. Moreover, perceived safety threat and outcome expectations have a positive impact on attitude; attitude has a positive impact on behavioural intentions; subjective norm has a positive impact on behavioural intentions, and perceived behavioural control has a positive impact on behavioural intentions. The study results identify practical and theoretical implications for global and travel companies and organisations, presenting opportunities to adjust environmental policies and procedures accordingly, whilst identifying the most effective marketing and management strategies to rebuild a collapsed global travel industry.